34 High intake of coffee positively correlated with total and LDL cholesterol in healthy young adults. (October 2018) - Condon, C; Rai, A; Tse, C; Derex-Briggs, J; Adoma Koduah-Sarpong, N; El-Sayed, T; Stanton, A
Abstract : It is known that coffee consumption has a J shaped relationship with mortality – while moderate coffee drinking may be protective, drinking more than 4 cups of coffee each day results in excess cardiovascular deaths. It has been suggested that this relationship may be due to coffee containing cholesterol raising diterpenes (cafestol and kahweol). Certainly higher cholesterol levels have been reported in middle-aged and older coffee drinkers. This study aimed to test if elevated cholesterol levels are also present in younger coffee drinkers. This was a cross-sectional study of 116 healthy students. All participants completed a 1 week coffee diary. Coffee consumption was quantified in expresso equivalents – a single expresso, 100 ml filtered coffee, or 1.5 teaspoons instant coffee, all contain approximately 75 mg caffeine. Fasting total, LDL and HDL cholesterol and triglycerides were measured. Age ranged from 18–34 years and coffee drinking habits ranged from 0–12 expresso equivalents/day. There were significant positive correlations between daily intake of coffee with both total and LDL cholesterol (correlation coefficients [p-values]; 0.24, [0.008], and 0.27 [0.004] respectively). Drinking just 1 Venti Starbucks Americano coffee per day (4 expresso equivalents) was on average associated with 0.3 mmol/L increments in both total and LDL cholesterol. Coffee is a widely consumed beverage worldwide, and coffee consumption habits are evolving towards drinking greater quantities of espresso based drinks, which contain higher quantities of diterpenes than filtered or instant coffee. Hence, our observation of a statistically significant positive correlation, of a clinically relevant magnitude, between coffee consumption and cholesterol, amongst young people, may have considerable implications for public health and demands further scrutiny.